1999
DOI: 10.1103/physrevb.60.8704
|View full text |Cite
|
Sign up to set email alerts
|

Multiple bonding configurations for Te adsorbed on the Ge(001) surface

Abstract: Using high-resolution x-ray standing waves and low-energy electron diffraction, the structure of Te adsorbed on Ge͑001͒ was studied. A coverage-dependent structural rearrangement was observed between Te coverages of 1 and 0.5 monolayer ͑ML͒. At Te coverages near 1 ML, Te was found to adsorb in a bridge site, as expected. However, at Te coverages near 0.5 ML, a structure unanticipated for Group VI/Group IV adsorption was discovered. Te-Ge heterodimers were formed with an average valency of 5, allowing them to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
74
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(74 citation statements)
references
References 36 publications
0
74
0
Order By: Relevance
“…3 unexpected observation implies that the structure of the interfacial layer at the Bi2Te3/Ge interface is that of an inverted Ge-Te dumbbell-like structure (QLBi2Te3/Ge/Te/ Gesub). It is interesting to note that experimental surface studies on Te monolayers on Ge(100) show the unusual formation of Te-Ge dimers, [34]which may also occur on the Ge(111) surface, thus providing the mechanism for inverted dumbbell formation. However, further studies are necessary to shed light on the mechanisms that drive the formation of the observed interface structure in our films.…”
Section: Resultsmentioning
confidence: 99%
“…3 unexpected observation implies that the structure of the interfacial layer at the Bi2Te3/Ge interface is that of an inverted Ge-Te dumbbell-like structure (QLBi2Te3/Ge/Te/ Gesub). It is interesting to note that experimental surface studies on Te monolayers on Ge(100) show the unusual formation of Te-Ge dimers, [34]which may also occur on the Ge(111) surface, thus providing the mechanism for inverted dumbbell formation. However, further studies are necessary to shed light on the mechanisms that drive the formation of the observed interface structure in our films.…”
Section: Resultsmentioning
confidence: 99%
“…Preferred structures for the temperature-dependent and coverage-dependent adsorption of Te on Ge͑001͒ can be listed as follows: ͑i͒ bridge site as revealed by XSW, SEXAFS, and STM measurements, 14 ͑ii͒ missing row model ͑MRM͒ with ͑5ϫ1͒ surface reconstruction as concluded by XSW, LEED, 19 and CRT, 16 ͑iii͒ MRM with ͑5ϫ2͒ geometry as suggested by the STM and the LEED measurements, 15 and backed by theory, 20 and ͑iv͒ c(2ϫ2) geometry as observed by AES 17 and confirmed by ab initio calculations. 23 In this work, we have attempted to study seven different configurations including ͑i͒, ͑ii͒, and ͑iv͒ mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…The final ͑1ϫ2͒ clean surface was attributed to the formation of a double-domain structure. Lyman et al 19 studied the multiple bonding configurations of Te adsorbed on the Ge͑001͒ surface by using high-resolution XSW and LEED. They observed that close to 1-ML coverage the adsorption takes place at the bridge site, and the 0.5-ML coverage gives rise to a c(2ϫ2) structure with Ge-Te heterodimers.…”
Section: Introductionmentioning
confidence: 99%
“…For the case of Te on Si͑001͒ and Ge͑001͒, experimental and theoretical results have shown that a completely dereconstruction of the surface to a (1 ϫ1) periodicity is not possible, due to the large size of Te atoms. [2][3][4][5][6] For S on Ge͑001͒, Weser et al were able to prepare a S/Ge(001)(1ϫ1) interface, showing that it is an ideally terminated surface. 7 They also showed that the sulfur coverage was one atom per Ge surface atom, with sulfur atoms bonded in bridge sites.…”
Section: Introductionmentioning
confidence: 99%